THE IMPACT OF SOCIAL MEDIA INFLUENCER AND BRAND IMAGES TO PURCHASE INTENTION - Nurhandayani, Arum; Syarief, Rizal; Najib, Mukhamad (Jurnal Aplikasi Manajemen, 2019)
Recent years was a magnificent evolution of the digital world. Some phenomenon comes from social media which drive the new ways of communication between a companies with their consumers. Often, they (companies) hired an influencer on social media to advertise their product. This study was designed to analyse the impact of social media influencer and brand image on consumer's purchase intentions. Female with millennial ages (15-34 years old) and living around Jakarta city were participated in this research using structured questionnaire. Structural equation modeling (SEM) was used to analyse the data collection. The result of this study hammering the current believes that it is true the medial social influencer has a significant impact on building the brand images, and it has positive correlation. But based on the study, using social media influencers to influence consumer's purchase intention was not giving a significant impact. It will help the brand to build a perceived image on consumer's minds then the brand image was driving their consideration to purchase.